Seed tannin composition of tropical plants. (July 2021) - Kim, Jorma; Gripenberg, Sofia; Karonen, Maarit; Salminen, Juha-Pekka
Abstract: Seeds collected from trees, shrubs and lianas growing on Barro Colorado Island, Panama, were analyzed for their content of phenolic compounds, oxidative activities and protein precipitation capacities. Proanthocyanidins and hydrolysable tannins were detected in one-third of 189 studied species. The most oxidatively active group of species were the ones containing prodelphinidins and ellagitannins whereas the species that had the highest protein precipitation capacity in relation to their total phenolics were the ones containing punicalagin. In addition, the oxidative activity and relative protein precipitation capacity were exceptionally high in the proanthocyanidin-rich genus Psychotria . This study offers a comprehensive overview on the tannin composition and the alkaline oxidative activities and protein precipitation capacities of the seeds of tropical plants. Graphical abstract: Image 1 Highlights: Tannins were detected in seeds of 63 species out of 195 collected and 189 analyzed. Species rich in prodelphinidins and ellagitannins had the highest oxidative activity. The protein precipitation capacity varied a lot between the species. Psychotria species rich in unidentified proanthocyanidins were exceptionally active.